(untitled) (Innovaciones Educativas, 2021)
This article contemplates the main results of the research, the purpose of which was to analyze the effectiveness of the resources and technological applications selected by the teaching population of the José Trinidad Mora Valverde School of Costa Rica, for the development of the pedagogical mediation processes in the period from July to September 2020. The research approach was mixed. Among the main results obtained, it stands out that teachers have prioritized cell phones as a technological resource for pedagogical mediation processes. This inasmuch as it is the means to which they have the best access and through which they have the best communication with children and parents. In addition, this group of participants shows a great commitment to generate effective spaces in order to favor pedagogical mediation, with the support of technologies. However, their little experience in the use of resources and technological applications for educational purposes is evident. Among the conclusions, it is highlighted that teachers are giving priority to the use of Microsoft Teams® and WhatsApp® technological applications for educational purposes, and for the “I learn at home” strategy implemented by the Ministry of Public Education, since these two applications are the most used by teachers. In addition, the need to strengthen training for the best use of the various technological applications available for teaching and learning processes is clear.